Meningkatkan Kecerdasan Interpersonal Anak Usia Dini Dengan Menggunakan Metode Bermain Peran - Pistos Manila (Peneliti.net, 2022)
The objectives of the research are: for the role of the role-playing method to improve the Interpersonal Intelligence of Early Childhood in Non-formal PAUD in Southeast Minahasa Regency. This research uses Classroom Action Research (CAR), as the sample is early childhood as many as 20 people consisting of 8 boys and 12 girls. Data were collected using observation, interview, and documentation techniques. Meanwhile, to analyze the data used percentage analysis techniques. The conclusion of the research is that the role playing method can increase the Interpersonal Intelligence of Early Childhood in Non-formal PAUD in Southeast Minahasa Regency by 72% (MB = Starting to Develop) in the first cycle and 95% (BB = Good development) in the second cycle. In connection with this research, it is suggested as follows: For parents as primary and first educators, they should be a good example for children both in words and actions. For educators (teachers) to place more emphasis on learning on the formation of affective aspects (morals, ethics, attitudes), it is hoped that there will be intense cooperation between: parents and educators (teachers) in children's education.